Influence of expositions - Drollinger, Della (My University, 1902)
Introduction: It would not be easy to overestimate the educational value of the objects of beauty, monumental architecture, galleries of painting and sculpture, and museums that are found in some of the old European towns, for such things, stimulate the imagination, increase a thirst for knowledge, and awaken and educate the aesthetic faculties. Much of the marvelous beauty and wealth of public architecture and art in small European towns has been due to earlier political conditions. The town at some time probably was the seat of government of some small kingdom, but in these days of great empires those old time motives have passed away and something new must take their place. The tendency to create expositions is a valuable part of the outworkings of these new motives.
Citation: Drollinger, Della. Influence of expositions. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Expositions; Exhibits; Museums; Theses; Manuscripts (documents)